Prevalence and determinants of children self-reports of food insecurity: evidence from a Portuguese population-based birth cohort
Children’s food insecurity has been associated with adverse health outcomes. In Portugal, data on children’s reports of food insecurity, as well as its determinants, are scarce. This study assessed the prevalence and determinants of children’s food insecurity in a population-based sample of Portuguese children. A cross-sectional study based on 2895 children from the Generation XXI birth cohort was performed. Data on food security status and socio-demographic characteristics were collected. Food security status was assessed through the Self-Administered Food Security Survey Module for Children Ages 12 Years and Older. Associations between children’s food insecurity and socio-demographic characteristics were explored using logistic regression models. The food insecurity prevalence was 9.5%. Boys (OR = 1.98; 95%CI = 1.51–2.59), children with low educated mothers (OR = 2.28; 95%CI = 1.62–3.20), fathers in low occupational positions (OR = 1.70; 95%CI = 1.19–2.43), from families with low income (OR = 1.53; 95%CI = 1.05–2.24) and children belonging to families with the perception of having an insufficient household income (OR = 2.54; 95%CI = 1.45–4.45) were more prone to food insecurity. Belonging to a stepfamily (OR = 1.82; 95%CI = 1.04–3.19), single-parent family (OR = 2.26; 95%CI = 1.56–3.28) or extended family (OR = 1.82; 95%CI = 1.28–2.59), and having caregivers unemployed (OR = 1.72; 95%CI = 1.30–2.28) were associated with children’s food insecurity. Household size (OR = 1.24; 95%CI = 1.06–1.45) also showed to be positively associated with food insecurity. Around one in every ten children were shown to be food insecure. Male children, with low educated mothers and fathers in low occupational positions, caregivers’ unemployment, belonging to stepfamilies, single-parent families or extended families, and families with a low and perception of insufficient household income may be those who would beneficiate the most from Public Health interventions to promote food security.